Beauty-Contests in the Age of Financialization: Information Activism and Retail Investor Behavior. (March 2018) - Rickett, Laura; Datta, Pratim
Keynes (The General Theory of Employment, Interest and Money, Harcourt Brace and Co., New York, 1936) had rightfully argued that picking stocks is akin to a beauty contest. The chances of winning are amplified if one's choice matches the likelihood of the panel's choice. In this era of financialization, where profit-making has shifted to speculative sways rather than fundamental trade and commodity production measures (Krippner, Socio-Econ Rev3 (2): 173-208, 2005), similar beauty contests have become even more acute. Online, real-time media channels along with pervasive investments applications have ushered in unprecedented online financial information and retail investor interest, ranging from dealing in penny stocks to sentiment-based trading. More than information sources, similar investment sites compete to recommend investment directions and strategies, not driven by strict fundamentals used by "arbitrageurs" or rational speculators but on pseudo-signals proffered by various information investment channels with varying degrees of credibility. This behavior, referred to herein as information activism, concomitantly adds a sociopsychological dimension to the concept of financialization (Lagoarde-Segot, Int Rev Financial Anal 2016) – wherein technology-driven information reach and range contribute to financial dominance of financial actors and practices. Using information activism as a lens, this research empirically evidences the extent to which information activism affects retail investor behavior under various market conditions. This study examines the differential effects of two primary, albeit reputable, sources of information activism: an investment news channel (CNBC – Mad Money) and an online financial blog (SeekingAlpha), and the effect on investor behavior during the 2008 financial crisis. In identifying the specific downstream effects of information activism on capital markets and investor behavior, factors related to investor behavior, such as trading volume and price reaction, are analyzed surrounding information activism events. Results indicate that retail investors appear to rely on online information activists during uncertain economic conditions. Findings denote that abnormal returns are associated with information activism during uncertain economic conditions and for buy recommendations when information asymmetry is high. Abnormal trading volume is also associated with information activism during economic uncertainty and with buy recommendations when information asymmetry is high particularly for stocks exchanges where unsophisticated investors tend to trade more heavily.